Pope Francis's Synod on synodality and modern sociology: exploring the Synod's behavioral and research aspects - Ballano, Vivencio O. (Routledge studies in religion, 2025)
"This book focuses on the value and necessity of modern sociology to Pope Francis's church reform project known as the Synod on Synodality. It explores the behavioral and research aspects of this latest synod, applying sociological perspectives and methods and drawing on secondary literature, media reports, and church documents. The author argues that sociology is crucial for translating the major theological concepts into behavioral and research indicators to empirically ground the overall theological framework of the synod as an ecclesial innovation rather than a revolution in the Catholic Church. The importance of sociological research methodology is emphasised to guide the synod's complex and multi-stage qualitative data collection, which seeks to understand the synodal concerns of all Catholics in today's world. The book addresses the need for scientific approaches to church reforms and for a nuanced complementarity between sociology and theology. It will be of particular interest to scholars of theology, religion, and sociology, as well as those actively involved in the workings of the Catholic Church"--